How much do cancer specialists earn? A comparison of physician fees and remuneration in oncology and radiology in high-income countries. Issue 2 (February 2018) - Boyle, Seán; Petch, Jeremy; Batt, Kathy; Durand-Zaleski, Isabelle; Thomson, Sarah
Highlights: Higher spending on healthcare in the USA is driven by higher physician fees. The oncology consultation fee is three times greater, chemotherapy four times. There is a three to fourfold variation in fees for ultrasound and CT scans. Physician earnings in the USA are greater in oncology and radiology. Canadian specialists earn considerably more than their European counterparts. Abstract: The main driver of higher spending on health care in the US is believed to be substantially higher fees paid to US physicians in comparison with other countries. We aim to compare physician incomes in radiology and oncology considering differences in relation to fees paid, physician capacity and volume of services provided in five countries: the United States, Canada, Australia, France and the United Kingdom. The fee for a consultation with a specialist in oncology varies threefold across countries, and more than fourfold for chemotherapy. There is also a three to fourfold variation in fees for ultrasound and CT scans. Physician earnings in the US are greater than in other countries in both oncology and radiology, more than three times higher than in the UK; Canadian oncologists and radiologists earn considerably more than their European counterparts. Although challenging, benchmarking earnings and fees for similar health care activities across countries, and understanding the factors that explain any differences, can provide valuable insights for policy makers trying to enhance efficiency and quality in service delivery, especially in the face of rising care costs.